Reallocation of Resources Across Age in a Comparative European Setting - Bernhard Hammer; Alexia Prskawetz; Inga Freund (WWWforEurope, 2014)
We investigate the reallocation of resources across age and gender in a comparative European setting. Our analysis is based on concepts and data from the National Transfer Accounts (NTA) project, as well as on data from income and time use surveys. We introduce the aggregate NTA life cycle deficit as a concept of an economic dependency ratio. This dependency measure allows for flexible age limits and age-specific levels of economic dependency. We then move beyond the current NTA methodology and study gender differences in the generation of income and extend our analysis by unpaid household work. We find large cross-country differences in the age- and gender-specific levels and type of production activities and consequently in the organisation of the resource reallocation across age. Our results clearly indicate that a reform of the welfare system needs to take into account not only public transfers but also private transfers, in particular the services produced within the households for own consumption (e.g. childcare, cooking, cleaning...).
Keywords: I38; J10; 330; Ageing; challenges for welfare system; demographic change; welfare state